2017
DOI: 10.31018/jans.v9i2.1281
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different levels of organic and inorganic fertilizers on growth, yield and quality of preseasonal sugarcane ratoon in Inceptisols

Abstract: A field experiment was conducted at soil test crop response (STCR) correlation project farm of Mahatma Phule Krishi Vidyapeeth, Rahuri Maharashtra.The result showed that individual application of nitrogen (N), phosphorus(P),potassium(K) or organic nutrient sources (Farm yard manure) recorded less value of preseasonal sugarcane ratoon but the integration of both the sources showed significantly improved all the growth, yield and quality parameters of preseasonal sugarcane ratoon. The maximum number of internode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
2
2
1
1
Order By: Relevance
“…The requirements for sugar cane to reach a yield of ca. 120 T/ha are 180, 60, and 230 kg/ha of N, P, and K, respectively; these values are similar to recommendations in other situations ( Leal et al, 2009 ; Blum et al, 2013 ; Ghube et al, 2017 ). The sugarcane yields are given in Supplementary Table 2 .…”
Section: Methodssupporting
confidence: 82%
“…The requirements for sugar cane to reach a yield of ca. 120 T/ha are 180, 60, and 230 kg/ha of N, P, and K, respectively; these values are similar to recommendations in other situations ( Leal et al, 2009 ; Blum et al, 2013 ; Ghube et al, 2017 ). The sugarcane yields are given in Supplementary Table 2 .…”
Section: Methodssupporting
confidence: 82%
“…Furthermore, the yields of the SV and SVM treatments were no higher than the yields of other treatments. Several studies have shown that soil potassium analyses are not well correlated with sugarcane yields [19,31,32]. In very clayey soils, such as the Nitisol in our study, potassium inputs above 225 kg•ha −1 did not increase yields [32].…”
Section: Effects Of Fertilisation Strategies On Yield or Soil Propertiescontrasting
confidence: 78%
“…The sugarcane vinasse came from the Bois-Rouge sugar factory (Saint-André, Reunion Island). Under Reunion Island conditions, to obtain a yield of 100 Mg•ha −1 , the N, P, and K requirements for sugar cane cultivation are, respectively, 120, 70 and 200 kg•ha −1 ; these values are similar to those recommended at other locations [19]. Each year, at the beginning of the growing cycle, plots under the organic treatment with synthetic mineral complementation received equivalent N and P nutrients to that provided in the control treatments.…”
Section: Field Experimentssupporting
confidence: 54%
“…Treatment 1 (6 Phonska + 5 ZA) and 2 (7.2 Phonska + 6 ZA) showed a lower growth rate of plant height compared to treatment 3 (8.4 Phonska + 8 ZA). Ghube [17] stated that N (150 -350 kg ha -1 ), P2O5 (65 -165 kg ha -1 ), and K2O (65-165 kg ha -1 ) fertilizer did not produce different plant heights. The treatment produced 301-365 cm plant height.…”
Section: Sugarcane Growth Componentsmentioning
confidence: 99%
“…The fertilization significantly increased the productivity level of CO 421 Variety. Ghube (2017) [17] stated that increasing superphosphate from 50 kg/ha to 150 kg/ha did not influence the total population. However, it can produce 30% higher than control (without P fertilizer).…”
Section: Components Of Sugarcane Production Productivity and Sugar Yieldmentioning
confidence: 99%